THE RELATIONSHIP BETWEEN NURSING STUDENTS’ TRANSFORMATIONAL LEADERSHIP STYLE AND THEIR SELF-REGULATION IN ASSUMPTION UNIVERSITY IN THAILAND - LIU, CHANGRUI; VINITWATANAKHUN, WATANA (Scholar: Human Sciences, 2022)
This study aimed to investigate the relationship between Transformational Leadership and Self-Regulation based on nursing students’ perceptions at Assumption University, Bangkok, Thailand. This study was conducted with 72 nursing students in the academic year 2020 – 2021. Three main objectives were included in this study. The first objective was to determine the level of nursing students’ Transformational Leadership Style. The second objective was to determine the level of nursing students’ Self-Regulation. The third objective was to determine if there is a relationship between nursing students’ Transformational Leadership Style and their Self-Regulation at Assumption University. The findings showed that the perceptions of nursing students toward Transformational Leadership presented at a high level, and the perceptions of nursing students towards Self-Regulation presented at a moderate level. The results demonstrated a moderate positive correlation, for the (r) value was .495** at the significant level of 0.000, which was less than 0.05 level, in the perceptions of nursing students.